Childbirth and women's labour market transitions in India (revised) - Rosa Abraham; Rahul Lahoti; Hema Swaminathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The impact of childbirth on women's employment has been discussed extensively in the context of developed countries. Constraints on mothers' labour market participation and consequent fall in earnings are characterised as the 'motherhood penalty'. This phenomenon is relatively less explored in developing countries primarily because of the lack of suitable data. In this paper, we use primary data from India, collected via a life history calendar administered to men and women separately. Using an event study method, we estimate the impact of the first childbirth on women's labour market participation. Our main finding is that the birth of the first child does not impose a penalty, in the traditional understanding, on a mother's labour supply. While overall employment does not show any association with childbirth, women's paid work registers a significant increase two to three years post childbirth. This impact is largely due to an increase in informal paid work and driven by women with lower levels of education and from relatively poorer households. Our results suggest that in a developing country like India, characterised by informal labour markets, and early age of childbirth, the impact of motherhood on employment may need an alternate framing rather than one based on developed countries.
Additional information: This publication is a revised version of WIDER Working Paper 2021/128: https://doi.org/10.35188/UNU-WIDER/2021/068-9 .
Keywords: J01; J12; J13; J16; 330; motherhood penalty; childbirth; event study; life history calendar; India